Re-profiling today's health care curricula for tomorrow's workforce: Establishing an interprofessional degree in Germany - Mahler, Cornelia; Berger, Sarah Jane; Karstens, Sven; Campbell, Stephen; Roos, Marco; Szecsenyi, Joachim (Journal of Interprofessional Care, 2015)
Laws regulating education of most health professional groups in Germany today mean that curricula re-profiling in response to changing priorities in the practice environment is a significant challenge. Legally dictated theoretical and clinical requirements for the vocational training of health professionals leaves little room for re-profiling in response to movements such as interprofessional education. An educational innovation was needed that worked within existing structures in Germany. The result was a formal collaboration between the Academy for Health Professionals and the University of Heidelberg allowing students undertaking vocational training to also complete a university degree in parallel. The aim of this article is to describe the curriculum development for the Bachelor of Science - Interprofessional Health Care. This article outlines an evidence-based approach to the process to curriculum development that resulted in a competency-based degree offering comprehensive interprofessional education at undergraduate level for healthcare students based in Germany.
EVALuna2:26306